A CLINICAL STUDY ON THE ROLE OF SHRINGYADI CHURNA AND GUDUCHYADI KWATHA IN THE MANAGEMENT OF TAMAKA SHWASA WITH REFERENCE TO BRONCHIAL ASTHMA - Seth, Kimmi; Singh, Om Prakash; Pandey, Punita; Singh, Deshraj (International Journal of Ayurveda and Pharma Research, 2015)
Tamaka Shwasa is one of the stressful medical conditions of todays era and is well known for its episodic and chronic course which afflicts the human race. It is analogous to Bronchial Asthma due to similarity in etiopathogenesis and symptoms. Though incidence of Tamaka Shwasa is increasing in day to day practice and at alarming rate but very few patients need intensive care and most of the patients can be managed effectively by Ayurvedic line of treatment. Ayurvedic medicine may help to decrease the recurrence, improve immunity, and check symptoms naturally. Aims and Objectives: To evaluate the efficacy of Shringyadi Churna and Guduchyadi Kwatha in the management of Tamaka Shwasa. Materials and Methods: 20 Patients suffering from Tamaka Shwasa and attending the O.P.D. and I.P.D. department of Kayachikitsa, Rishikul Campus Haridwar were selected randomly. Patients were investigated as per proforma prepared for the study. Shringyadi Churna is given with Guduchyadi Kwatha as Anupana dravya for duration of 4 weeks, with assessment follow ups of 15 days interval and follow up was done after 2 months of the completion of the trial. All the patients were kept under strict dietary control during the treatment. Results and Discussion: The observation of the effect of therapy was encouraging and reduced recurrence significantly. Out of 20 patients, 16 patients i.e. 80% patients attained Marked Improvement in the symptoms, 1 patient i.e. 5% attained Moderate improvement in symptoms whereas In 3 patients i.e. 15% attained Complete remission of the symptoms of Tamaka Shwasa.